Implementasi Monero Mining Pada Raspberry Pi 4 Model B - Muhammad Derri Fadilah; Hafiz Firdaus; Muhamad Riyyan (Department of Science and Technology Ibrahimy University, 2023)
In the world of cryptocurrency, Monero is one of the cryptocurrencies that was created in 2014. Monero uses CryptoNight as a proof-of-work algorithm to get cryptocurrency coins. The proof-of-work algorithm requires miners to have tools with large computing power so they are competing to buy tools with large computing power, but there is a problem with the electricity generated is also large. The Raspberry Pi was tested as an alternative cryptocurrency mining tool that has economic value. In this study, we implemented the Raspberry Pi 4 Model B to calculate how much computing power was generated and how to mine using this tool. The design of this system makes the tool made quite compact and efficient which helps the convoluted mining process. The rising trend of cryptocurrencies has resulted in an increasing demand for economical mining tools. The Raspberry Pi crypto mining system helps provide an economical and energy efficient tool.